2005
DOI: 10.1007/s00441-005-0080-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical evidence for glutamatergic transmission in primary sensory neurons and onto postganglionic neurons controlling penile erection in rats: an ultrastructural study with neuronal tracing and immunocytochemistry

Abstract: In male rats, the dorsal penile nerve (DPN) conveys sensory information from the genitals to the lumbosacral spinal segments of the spinal cord. DPN is the afferent limb of a reflex loop that supports reflexive erections, and that includes a network of spinal interneurons and autonomic and somatic motoneurons to the penis and perineal striated muscles. Autonomic efferent pathways to the penis relay in the major pelvic ganglion (MPG). Glutamate (Glu) is a likely candidate as a neurotransmitter of reflexive erec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Markers of glutamatergic axons, in conjunction with peripherin (a Class III intermediate filament subunit protein that identifies small DRG neurons and their processes) (Parysek and Goldman, 1988; Goldstein et al, 1991; Lee et al, 2002), were shown in sensory nerves of the cervix. Retrograde tracing in the present study supports the idea that sensory glutamatergic neurons extend axons to innervate visceral pelvic organs (Keast and Stephensen, 2000; Aioun and Rampin, 2006) and that glutamate is localized, and presumably synthesized, in primary afferent neurons of DRG (Wanaka et al, 1987; Battaglia and Rustioni, 1988; Kai‐Kai and Howe, 1991; Miller et al, 1993; Keast and Stephenson, 2000; Ghosh et al, 2006). Nerve‐crush studies indicate glutamate is transported peripherally and centrally from DRG cell bodies (Keast and Stephensen, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…Markers of glutamatergic axons, in conjunction with peripherin (a Class III intermediate filament subunit protein that identifies small DRG neurons and their processes) (Parysek and Goldman, 1988; Goldstein et al, 1991; Lee et al, 2002), were shown in sensory nerves of the cervix. Retrograde tracing in the present study supports the idea that sensory glutamatergic neurons extend axons to innervate visceral pelvic organs (Keast and Stephensen, 2000; Aioun and Rampin, 2006) and that glutamate is localized, and presumably synthesized, in primary afferent neurons of DRG (Wanaka et al, 1987; Battaglia and Rustioni, 1988; Kai‐Kai and Howe, 1991; Miller et al, 1993; Keast and Stephenson, 2000; Ghosh et al, 2006). Nerve‐crush studies indicate glutamate is transported peripherally and centrally from DRG cell bodies (Keast and Stephensen, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…The present results support the notion of expression of glutamate in nerve fibers innervating the MPG and also forming perineuronal baskets. Finally, in their study, Aïoun and Rampin also reported that the distribution and appearance of glutamatergic terminals in the MPG was similar to those of retrogradely traced penile sensory nerve terminals in this ganglion, targeting a specific subset of MPG neurons (Aïoun and Rampin 2006). Whether this is the case in our present work in mouse requires further investigation.…”
Section: Discussionmentioning
confidence: 67%
“…These are typically cholinergic, and often coexpress other transmitters, including neuropeptides (de Groat 1987; Wanigasekara et al, 2003; Keast 2006). Evidence of a glutamatergic trait in MPG perineuronal baskets has not been reported previously, with the exception of an electron microscopy study in rat showing glutamate in axons and terminals in the MPG, also containing large dense core vesicles (Aïoun and Rampin 2006). However, and possibly because of the nature of the experimental approach (electron microscopy), the authors did not assess the presence of perineuronal baskets containing glutamate in the MPG.…”
Section: Discussionmentioning
confidence: 80%
“…The afferent inputs that trigger activation of NMDA receptors in LSt cells are currently unknown, although the most likely activation of LSt cells is via DPN nerve fibers. The densest distribution of DPN sensory afferent terminals is located in the superficial laminae of the L5 and L6 lumbar segments [17] and glutamate is expressed in DPN sensory afferents in male rats [12]. Stimulation of the pudendal nerve results in increased Fos‐immunoreactive nuclei in the L5‐S1 spinal segments, with the majority of these nuclei being located in the superficial dorsal horn and the central gray area in the DGC [18].…”
Section: Discussionmentioning
confidence: 99%